Market Research – Health Literacy's Missing Ramp. Issue 1 (2nd January 2022) - Stone, William; Faughnan, Juliette C.
ABSTRACT: With only about 12% of U.S. adults having what is considered proficient health literacy, a plain language "universal precautions" approach toward the writing of patient education materials is warranted. In practice, however, this is seldom done. One persistent reason for this is that the market research that informs the writing of patient education materials frequently ignores respondent health literacy levels when setting quotas and recruiting participants. Since market research respondents traditionally have higher levels of health literacy, this can result in patient education materials that are too complex for optimal accessibility and comprehension. CHES and MCHES professionals have both an opportunity and a responsibility to hold pharmaceutical companies and market researchers accountable and encourage them to incorporate diverse patient voices reflecting a wide range of health literacy levels in their studies.